The Influence of Football Boot Construction on Ball Velocity and Deformation - M. A., Aris; Zahari, Taha; M. H. A., Hassan (2013)
Running footwear research on the biomechanical properties of football boots has received little scientific attention. Recently, modern and scientific football boots has been developed that affords excellent ball control, shooting and running ability. Different construction of football boots delivers different velocity and deformation of the ball. In this study, three commercially available football boots were compared during kicking experiment in terms of, ball velocity and deformation of the ball. A subject performed three repetitive shots of the ball into the net for each football boot model. The footballer foot and the ball velocity were recorded using a high speed camera. From the recorded video, the kicking velocity, ball velocity and ball deformation were measured. Based on the foot and ball velocity data, the Coefficient of Restitution (COR) was calculated. The results obtained show the COR value varies with different boots (CORbootA = 0.89, CORbootB = 0.59, CORbootC = 0.47) thus delivers different ball velocities at same kicking foot velocity (Uleg = 14 ms-1). It is apparent that the Boot A was made with the best upper material (Teijin synthetic leather), design and also construction of the boot.